2020
DOI: 10.1136/bmjgh-2020-002475
|View full text |Cite
|
Sign up to set email alerts
|

Universal access to essential health information: accelerating progress towards universal health coverage and other SDG health targets

Abstract: The information that people need to protect and manage their own health and the health of those for whom they are responsible is a fundamental element of an effective people-centred healthcare system. Achieving universal health coverage (UHC) requires universal access to essential health information. While it was recently recognised by the World Medical Association, universal access to essential health information is not yet reflected in official monitoring of progress on UHC for the sustainable development go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Given the importance of the successful dissemination of information in public health, it is useful to look at the characteristics that contribute to this success. Some have argued that, for its dissemination to be successful, information has to be applicable, diverse, reliable, and comprehensible [ 5 ]. Among other things, applicable information refers to information that is relevant for tackling a health issue and appropriate to local practice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of the successful dissemination of information in public health, it is useful to look at the characteristics that contribute to this success. Some have argued that, for its dissemination to be successful, information has to be applicable, diverse, reliable, and comprehensible [ 5 ]. Among other things, applicable information refers to information that is relevant for tackling a health issue and appropriate to local practice.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse information targets a variety of people who might have different needs (such as children, adolescents, adults, pregnant women, and older people). Reliable information is based on evidence [ 5 ] and enables the individual to better protect him/herself and thus experience a sense of mastery of the situation. A Chinese study concluded that “erroneous knowledge could lead to ineffective preventive measures by the population and increase the risk of infection” (p. 302) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 29 of our respondents in their comments welcomed more training, workshops and online courses for surgical care topic in public health. The positive impact of wider access of actionable health information has already been shown [29] and we should use this example to do more to help disseminate the information from the publications [3][4][5] in a simplified, and freely accessible manner such as via factsheets or toolkits [30], visual imagery [31] or public health education courses. We need to learn from other successful public health advocacy programmes [32,33] in order to increase the visibility of surgical care.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, poor health literacy is associated with poor health outcomes, age, income, employment status, and a low level of literacy. This is why the WHO has made literacy a priority initiative to accelerate the achievement of the SDGs [29]. In the African context, special attention must be paid to rural areas if the UN hopes to achieve the SDGs by 2030, as around 656 million people live in such areas (about six in ten people) according to the World Bank [30].…”
Section: Enhancing Health Literacy In Rural Areas With Mobile Technolmentioning
confidence: 99%